Embedding academic literacies in university programme curricula: a case study. Issue 7 (2nd July 2016) - Murray, Neil; Nallaya, Shashi
Abstract : As the number of students entering higher education continues to increase, many English-medium universities have been looking carefully at how to more effectively ensure that those for whom English is not a first language have the opportunity to develop the academic literacies they require to successfully engage with and complete their studies as communicatively competent individuals. Their efforts, in part, reflect concern at the language problems faced by a (sometimes significant) proportion of this cohort, despite their having met English language entry criteria typically stipulated in terms of scores on high-stakes 'gatekeeping' tests such as IELTS. This article describes an approach adopted at an Australian university characterised by a very diverse student body. It takes as its starting point the notion that all students require tuition that helps them develop conversancy in the academic literacies of their particular disciplines and that such tuition should thus be embedded in the curriculum.